PENGARUH PROFITABILITAS, FIRM SIZE, DAN LEVERAGE TERHADAP MANAJEMEN LABA - William, Carla; Tjakrawala, F.X. Kurniawan (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study was to determine the effect of profitability, firm size and leverage on earnings management. This research uses secondary data and quantitative research as the type of research is. In this study, the population are LQ 45 companies which are listed on the website of Indonesia Stock Exchange for the period 2016-2021. The total sample reached 138 data and the method chosen when taking the sample was using the purposive sampling method. This research is also assisted by using SPSS 25. Based on the results obtained from the study, it shows that profitability and leverage partially have a significant effect on earnings management. Firm size partially has no significant effect on earnings management. Simultaneously (together) the variables of profitability, firm size and leverage have a significant effect on earnings management.